PRIVATE PROSECUTION AS A MEANS OF VINDICATING FUNDAMENTAL RIGHTS AND REINFORCING ACCOUNTABILITY IN A NASCENT CONSTITUTIONAL DEMOCRACY - Nkosi, Bongani S (Journal of Anti-Corruption Law, 2024)
The dawn of democracy had not only heralded respect and protection of human and fundamental rights, but also grand scale corruption committed among others by politicians and civil servants. Notwithstanding the highest rate of corruption by representatives of the public in almost all spheres of government, state owned enterprises and government departments, the rate of prosecution is truncated. Corruption inhibits the state from providing basic services such as water, electricity, access to healthcare, access to housing, infrastructure, and sanitation. The scourge of corruption affects every aspect of human life and has heightened even with the emergence of the corona virus pandemic. Corruption need not be grand scale to be reported and or prosecuted. Instances of corruption may include a councillor selling food parcels intended to benefit flood victims, a public officer being paid to employ civilians in the Extended Public Works Program, a traffic officer accepting a bribe from a motorist in return for not issuing a ticket for skipping a stop sign, a magistrate accepting sexual favour from a litigant in a case he presides over. In the event the National Prosecuting Authority declines to prosecute corruption, private prosecution remains the only recourse that civilians may resort to vindicate fundamental rights in a nascent democracy.